RESEÑA de : Eamon Duffy, Fires of Faith. Catholic England under Mary Tudor, New Haven and London, Yale University Press, 2009, 249 pp. ISBN. 978–0-300–15216–6. - García Hernán, Enrique (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2015)
RESEÑA de : Eamon Duffy, Fires of Faith. Catholic England under Mary Tudor, New Haven and London, Yale University Press, 2009, 249 pp. ISBN. 978–0-300–15216–6.